The Oxford illustrated history of modern China - Wasserstrom, Jeffrey N (Oxford Universiry press, 2017)
"This lavishly illustrated volume explores the history of China during a period of dramatic shifts and surprising transformations, from the founding of the Qing Dynasty (1644-1912) through to the present day. The Oxford Illustrated History of Modern China promises to be essential reading for anyone who wants to understand this rising superpower on the verge of what promises to be the 'Chinese century,' introducing readers to important but often overlooked events in China's past, such as the bloody Taiping Civil War (1850-1864), which had a death toll far higher than the roughly contemporaneous American Civil War. It also helps readers see more familiar landmarks in Chinese history in new ways, such as the Opium War (1839-1842), the Boxer Uprising of 1900, the rise to power of the Chinese Communist Party in 1949, and the Tiananmen protests and Beijing Massacre of 1989. This is one of the first major efforts--and in many ways the most ambitious to date--to come to terms with the broad sweep of modern Chinese history, taking readers from the origins of modern China right up through the dramatic events of the last few years (the Beijing Games, the financial crisis, and China's rise to global economic pre-eminence) which have so fundamentally altered Western views of China and China's place in the world"--Publisher description.